Artificial intelligence-based language learning: illuminating the impact on speaking skills and self-regulation in Chinese EFL context - Qiao, Hongliang; Zhao, Aruna (Frontiers in Psychology, 2023)
This study explored the effectiveness of an artificial intelligence-based instruction on second language (L2) speaking skills and speaking self-regulation in a natural setting. A randomized controlled trial was conducted with 93 Chinese English as a foreign language (EFL) students, randomly assigned to either the experimental group receiving an instruction based on artificial intelligence (AI) or the control group receiving traditional instruction. The AI-based instruction utilized the Duolingo application, incorporating natural language processing technology, interactive exercises, personalized feedback, and speech recognition technology. Pre-and posttests were conducted to assess L2 speaking skills and self-regulation abilities. The results indicated that the experimental group showed significantly greater improvement in L2 speaking skills than the control group, and participants in the experimental group reported higher levels of selfregulation. These findings suggest that AI-based instruction effectively enhances L2 speaking skills and fosters self-regulatory processes among language learners, highlighting the potential of AI technology to optimize language learning experiences and promote learners' autonomy and metacognitive strategies in the speaking domain. Further research is needed to explore the longterm effects and specific mechanisms underlying these observed improvements.